Interaksi Keberagamaan Dakwah Muhammadiyah di Kota Makassar - Nursalam Nursalam; Suardi Suardi (Universitas Muhammadiyah Makassar, 2017)
Abstract. This research is funded by the Muhammadiyah grant scheme. The purpose of this research in general is to examine the resources of Muhammadiyah da'wah. The type of this research is qualitative, the determination of informant research done by purposive sampling technique and snowball sampling. Data collection techniques through participant observation, in-depth interviews, documentation and participatory, research data will be analyzed through data reduction, display data, conclusion drawing and conclusion drawing. Data validity technique uses internal validity test, external validity, Dependency. Certainty / objectivity, and Triangulation (source, technique and time). The result of the research shows that to become dai Muhammadiyah that is (1) is a cadre, (2) active in organization, (3) recommendation from Branch or branch leader, (4) pass administration selection, (5) pass the reading ability test of Qur'an and the ability to perform lectures or khutbah. Competence must be owned by dai Muhammadiyah that is (1) understand Al Qur'an and hadith, (2) have science and education, (3) follow training. The form of the dai Muhammadiyah model is divided into three forms namely the serious da'wah model, the model of da'wah homoris and the model of serious and humorous combined da'wah. Propagation material muhammadiyah includes 7 material that is aqidah, morals, dates, general studies, special studies and Masail fiqhiyyah. The role of dai includes the mastery of social media, regeneration of dai, understanding of da'wah maps, efficiency of time, conduct study and reading.Keywords: Interaction, Dakwah, Muhammadiyah